Answer:
<em>a) 15 b) 6 c) -3</em>
Step-by-step explanation:
x - y = 3
a) 5 (x - y) = 5 (3) = 15
b) 2x - 2y = 2 (x - y) = 2 (3) = 6
c) y - x = -1 (x - y) = -1 (3) = -3
Answer:
77
Step-by-step explanation:
because im smart btw no treats involved
Answer:
um what kinda question is this?
Step-by-step explanation:
Answer:
y = -(x + 5)² + 4
Step-by-step explanation:
The roots are -3 and -7, so:
y = a (x + 3) (x + 7)
Distribute and complete the square:
y = a (x² + 10x + 21)
y = a (x² + 10x + 25 − 4)
y = a (x² + 10x + 25) − 4a
y = a (x + 5)² − 4a
The vertex is (-5, 4), so a = -1.
y = -(x + 5)² + 4
The slope is 0 I’m pretty sure because it is a horizontal line, if it was a vertical line it would be undefined